Mitigation of Bribery of Pharmacy Companies With Doctors in Review of Indonesian Anti-Corruption Law - Tias Dwi Okmalasari; Satria Unggul Wicaksana Prakasa (Faculty of Law, Muhammadiyah University of Surabaya, 2023)
At the end 2015 team​ Tempo Magazine was successful reveal exists case bribery committed by one​ company pharmacy that is Interbat against 2,125 doctors (Kompas , 2015). The indicator is the more the height price medicine and services health If We use service doctor (May T, 2017). Bribery the given in form of money and facilities other , Interesting sake Avoid KPK variations bribe No just money, but in form of sponsorship ( Prihartini , et.al, 2020). This is also caused interest financial from company pharmaceutical order for the drug to be produced in demand sold on the market . Apart from status doctor Civil Servant , profession There are also doctors with status as doctor private sector is opening place practice independent ( Fitri Z, 2018). Laws in circulation only status doctor​ Only civil servants can be ensnared​ with the Corruption Law , even though Non- State Servant doctors or doctor private sector can also snared with the Code of Ethics Law profession medicine ( Handayani , 2021). This research answers the questions (1) What is the influence of the form of bribery mitigation carried out by pharmaceutical companies with doctors? (2) How effort law in prevention And enforcement practice bribes to doctors by companies pharmacy in anti- corruption law Indonesia ? In research This writer use method research sociolegal with aspect review of the political economy of law that uses approach interdisciplinary , Research results This reveal that there is influence giving something to doctor by the company pharmacy to freedom and independence doctor in write recipe drug to patient as well as form of legal action for the receiving doctor bribe can snared with deed arranged bribes​ in articles 12B and 12C of the law Corruption ( action criminal corruption ) and prevention efforts bribe with ISO 37001:2016. Keywords : Pharmaceutical Companies, Bribery , Doctors